THE CORRELATION BETWEEN BULLYING EXPERIENCE AND SELF-ESTEEM LEVELS AMONG STUDENTS - Mustofa, Devi Afrianti; Anggih Permata; Ayu Apriliah; Dimas Aulia Akbar (CV. Doki Course and Training, 2023)
This study aimed to investigate the correlation between bullying experiences and the level of self-esteem among psychology students at UIN Raden Fatah Palembang. A quantitative research method was employed, utilizing a descriptive correlational design and a cross-sectional approach. The sample consisted of 40 fourth-semester students, with 5 males and 35 females, selected through simple random sampling. Bullying experiences were assessed using a 38-item Likert scale developed by Coloroso, while self-esteem levels were measured using a self-confidence instrument by Lauster (as cited in Mukti, 2013). The data analysis revealed a significance value (Sig. 2-tailed) of 0.790. As this value exceeds the significance level of 0.05, it indicates a lack of significant correlation between bullying experiences and the level of self-esteem among psychology students at UIN Raden Fatah Palembang.